ACE and Research: The Difference Between “Mere Press Agent” and Strategic Partner - Elizabeth North (Journal of Applied Communications, 2019)
ACE President Elizabeth Gregory North comments on JAC as evidence of the strong research tradition that is alive and well in ACE.